Outcome of Ipsilateral Ulnar Artery Cannulation in Failed Ipsilateral Radial Cannulation - Wahab; Yousaf, Hussnain (Indus Journal of Bioscience Research, 2024)
Objectives: This report aimed to assess the success rate of utilizing an ipsilateral ulnar artery where attempted or when added in conjunction with the attempted or used radial artery approach. Materials and Methods: An exploratory quantitative methodology is being followed in a prospective, observational study design of six months conducted at a tertiary care hospital in Pakistan. A convenient sample of 50 patients with failed radial artery cannulation was used. Ulnar artery cannulation was performed using ultrasound. Patients who required arterial access were adults and were excluded if they had known ulnar artery disease. The procedural success, the incidence of procedural-related complications, and the time to return to daily activities were measured. Results: The ipsilateral ulnar artery cannulation rate was 94%, with very few complications, including hematoma (4%) and arterial spasm (2%). Dissections of the nerves and arterial thrombosis were not observed. Most patients had a brief hospital stay and were discharged within 24 to 48 hours. Outcome assessment at 30 days postoperative did not reveal any serious complications lasting several months postoperatively. Conclusion: Ipsilateral ulnar artery cannulation is a safe and efficient approach as radial entry, with high success rates, low complication rates, and quick postprocedural recovery.